2019
DOI: 10.1002/term.2938
|View full text |Cite
|
Sign up to set email alerts
|

Composite clinoptilolite/PCL‐PEG‐PCL scaffolds for bone regeneration: In vitro and in vivo evaluation

Abstract: In this study, clinoptilolite (CLN) was employed as a reinforcement in a polymer-based composite scaffold in bone tissue engineering and evaluated in vivo for the first time.Highly porous, mechanically stable, and osteogenic CLN/PCL-PEG-PCL (CLN/PCEC) scaffolds were fabricated with modified particulate leaching/compression molding technique with varying CLN contents. We hypothesized that CLN reinforcement in a composite scaffold will improve bone regeneration and promote repair. Therefore, the scaffolds were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Up to date, ceramic‐based scaffolds, 2–6 synthetic thermoplastic polymeric scaffolds, 7–10 or their composites 8,11–13 have widely been employed to satisfy the mechanical characteristics of the native bone tissue. In recent years hydrogels have become a prominent choice of material thanks to their significant intrinsic resemblances to a natural extracellular matrix 14–22 .…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, ceramic‐based scaffolds, 2–6 synthetic thermoplastic polymeric scaffolds, 7–10 or their composites 8,11–13 have widely been employed to satisfy the mechanical characteristics of the native bone tissue. In recent years hydrogels have become a prominent choice of material thanks to their significant intrinsic resemblances to a natural extracellular matrix 14–22 .…”
Section: Introductionmentioning
confidence: 99%
“…CLN improved high quality bone union, cortical growth, and bone-scaffold interaction at the lesion location. These findings demonstrated that CLN in a composite scaffold promotes bone regeneration and aids in bone repair ( Pazarceviren et al, 2017 ; Pazarceviren et al, 2020 ). Recently, CLN was utilized as a food supplement to aid with bone development.…”
Section: Applications Of Zeolites In Bone Tissue Engineeringmentioning
confidence: 87%
“…Linna Zhong et al employed 3D printing extrusion to introduce nanoZIF-8 into polycaprolactone (PCL) and dicalcium phosphate dihydrate (DCPD) composite scaffolds to increase mechanical strength. They may also stimulate osteogenic differentiation of stem cells in vitro without the use of any other osteogenic agent and can steadily improve elastic modulus ( Hao et al, 2019 ; Pazarceviren et al, 2020 ). As shown in Figure 8 , uni-cortical tibial defects treated by scaffolds with zeolite in different concentrations have been compared.…”
Section: Applications Of Zeolites In Bone Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, PCL, like many synthetic polymers, is hydrophobic, which limits its polymer-cell interaction [86,87]. Generally, PCL is used as one of the material components [88,89], so minerals such as hydroxyapatite (HA), tetracalcium phosphate (TCP), etc. [90][91][92] are added to the composites to improve the mechanical strength of PCL scaffolds.…”
Section: Poly (ε-Caprolactone)mentioning
confidence: 99%